2009
DOI: 10.1038/npp.2009.171
|View full text |Cite
|
Sign up to set email alerts
|

α-Conotoxin MII-Sensitive Nicotinic Acetylcholine Receptors in the Nucleus Accumbens Shell Regulate Progressive Ratio Responding Maintained by Nicotine

Abstract: β2 subunit containing nicotinic acetylcholine receptors (β2*nAChRs; *denotes assembly with other subunits) are critical for nicotine self administration and nicotine-associated dopamine (DA) release that supports nicotine reinforcement. The α6 subunit assembles with β2 on DA neurons where α6β2*nAChRs regulate nicotine-stimulated DA release at neuron terminals. Using local infusion of alpha-conotoxin MII (α-CTX MII), an antagonist with selectivity for α6β2*nAChRs, the purpose of these experiments was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 59 publications
5
105
0
Order By: Relevance
“…Furthermore, we provide the first evidence for an important role of a6b2* nicotinic receptor subtypes in the rewarding effects of cocaine in the mouse CPP test. These findings are consistent with the high expression of a6* nAChRs subtypes in midbrain catecholaminergic nuclei that can regulate dopamine release (Grady et al, 2002;Whiteaker et al, 2000) and mediate nicotine reward and reinforcement in rodents (Pons et al, 2008;Jackson et al, 2009, Brunzell et al, 2010Gotti et al, 2010;Drenan et al, 2008).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Furthermore, we provide the first evidence for an important role of a6b2* nicotinic receptor subtypes in the rewarding effects of cocaine in the mouse CPP test. These findings are consistent with the high expression of a6* nAChRs subtypes in midbrain catecholaminergic nuclei that can regulate dopamine release (Grady et al, 2002;Whiteaker et al, 2000) and mediate nicotine reward and reinforcement in rodents (Pons et al, 2008;Jackson et al, 2009, Brunzell et al, 2010Gotti et al, 2010;Drenan et al, 2008).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the a6b2* nAChR antagonist given into the NAc completely blocked the development of nicotine CPP. Collectively, our results showing that a6b2* nAChRs in the NAc have a critical role in nicotine-conditioned reward concur with several studies including that by Brunzell et al (2010) who observed that inhibiting a6b2* nAChRs in the NAc shell significantly reduced motivation to self-administer nicotine, and those of Exley et al (2008; who observed that a6b2* nAChRs responses dominate in the NAc. However, others studies showed that the VTA is the primary site for nicotine reinforcing effects (Pons et al, 2008, Gotti et al, 2010.…”
Section: A6* Nachrs Subtypes In Nicotine Cppsupporting
confidence: 79%
See 2 more Smart Citations
“…Targeted gene deletion of α 6 abolishes and selective reexpression of α 6 in the VTA restores nicotine self-administration in mice (27). In addition, inhibition of α 6 * nAChRs on the terminals of VTA dopaminergic neurons through administration of αCTXMII into the NAc decreases the breaking point for nicotine responding in rats (38). As demonstrated here, down-regulation of α 6 * nAChRs impairs nicotine enhancement of evoked dopamine release in mouse NAc slices, whereas in vivo administration of αCTXMII into the VTA of rats attenuates nicotine-induced dopamine release in the NAc (39).…”
Section: Discussionmentioning
confidence: 99%